Mapping of interaction domains of putative telomere-binding proteins AtTRB1 and AtPOT1b from Arabidopsis thaliana - Schrumpfová, Petra Procházková; Kuchar, Milan; Palecek, Jan; Fajkus, Jirí (FEBS letters, 2008)
We previously searched for interactions between plant telomere-binding proteins and found that AtTRB1, from the single-myb-histone (Smh) family, interacts with the Arabidopsis POT1-like-protein, AtPOT1b, involved in telomere capping. Here we identify domains responsible for that interaction. We also map domains in AtTRB1 responsible for interactions with other Smh-family-members. Our results show that the N-terminal OB-fold-domain of AtPOT1b mediates the interaction with AtTRB1. This domain is characteristic for POT1- proteins and is involved with binding the G-rich-strand of telomeric DNA. AtPOT1b also interacts with AtTRB2 and AtTRB3. The central histone-globular-domain of AtTRB1 is involved with binding to AtTRB2 and 3, as well as to AtPOT1b. AtTRB1-heterodimers with other Smh-family-members are more stable than AtTRB1-homodimers. Our results reveal interaction networks of plant telomeres.
Keywords: proteiny huseníčku; Dimerization; Humans; Telomere-Binding Proteins; klonování DNA; lidé; interakční proteinové domény a motivy; Molecular Sequence Data; molekulární sekvence - údaje; dimerizace; Two-Hybrid System Techniques; proteiny vázající telomery; Arabidopsis Proteins; Cloning, Molecular; techniky dvojhybridového systému; Protein Interaction Domains and Motifs; Amino Acid Sequence; sekvence aminokyselin